2021
DOI: 10.3389/fnut.2021.647823
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Consumer Acceptance of Biofortified Food: Case of Zinc-Fortified Wheat in Pakistan's Punjab Province

Abstract: Zinc (Zn) is a fundamental micronutrient required by all living organisms. Zn deficiency among children under 5 years, pregnant, and child-bearing women has been identified in developing countries such as Pakistan. Biofortified crops can increase micronutrient levels and decrease deficiencies. Meanwhile, consumer acceptance is essential, given that genetic alterations can occur during biofortification, resulting in changes in sensory traits and the quality of grains. Therefore, the present study focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This finding suggests that adherence to the study intervention was likely to be high and aids our interpretation of the main RCT outcomes. The findings are also consistent with a previous study conducted in Pakistan in which participants tasted and rated chapati produced with biofortified wheat and conventional wheat very similarly in terms of sensory characteristics [23]. While differences in the scores were minor, Rizwan and colleagues found that the participants gave better scores to the chapati produced with biofortified wheat in terms of appearance and aroma while the conventional variety was scored slightly higher in terms of taste and texture.…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that adherence to the study intervention was likely to be high and aids our interpretation of the main RCT outcomes. The findings are also consistent with a previous study conducted in Pakistan in which participants tasted and rated chapati produced with biofortified wheat and conventional wheat very similarly in terms of sensory characteristics [23]. While differences in the scores were minor, Rizwan and colleagues found that the participants gave better scores to the chapati produced with biofortified wheat in terms of appearance and aroma while the conventional variety was scored slightly higher in terms of taste and texture.…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that the product idea appeals to a relatively broad consumer base in this respect. In contrast, many other studies have found that the willingness to try new functional foods decreases with age and increase with education level [54][55][56][57][58]. However, there are also contradictory reports in the literature [29,49].…”
Section: Target Groups Of Iodine-biofortified Fresh Produce Versus Di...mentioning
confidence: 95%
“… 85 , 86 More recently, Rizwan et al. 87 found that there is significant scope for promoting zinc wheat in the country.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in rural Uganda revealed that when nutrition information on the benefits of vitamin A sweet potato was provided, consumers valued the vitamin A-rich orange varieties more than white ones. 85,86 More recently, Rizwan et al 87 found that there is significant scope for promoting zinc wheat in the country.…”
Section: Consumer Understanding and Best Methods To Promote To Consumersmentioning
confidence: 99%